Determinantes da aglomeração espacial da atividade industrial no Estado de São Paulo - Bonini, André Leme da Silva Fleury (2015)
The globalization of capital and the process of globalization are largely responsible for increasing competitiveness. On one hand, firms strategically seeking the best location to optimize the costs of production and distribution, on the other, local governments compete to create the most appropriate basket of opportunity to postulate the attraction of new private businesses. Under the vision of the New Economic Geography (NEG), this paper measures the indicators of geographical concentration maps and the spatial location of where they are established major industrial clusters of the State of São Paulo. Also investigates what are the positive externalities, or centripetal forces that lead to agglomeration of activities, and the negative externalities, or centrifugal forces, which lead to spreading of investments. To this end, this research presents estimates cross section, which incorporates the contributions of theories of endogenous growth. The model is evaluated empirically through several variables by means of an application to the cities of São Paulo in 2010. The main results show that the number of industries and the population with at least upper level of completed graduation, positively influence the agglomeration. Have the greater the distance of the town to the capital, the less likely the occurrence of agglomeration. The conclusion we reached is that the municipal level, the agglomeration of industries is a sufficient condition for attracting new businesses and is consistent with the clusters theory proposed by Krugman (1997), while in micorregion level demonstrate the relevance of skilled human capital as a determining factor in the location of industries, supporting ideas by Porter (1989). We recommend that municipalities acting cooperatively, can outperform the indicators that determine the formation of the industrial GDP and thus become more attractive for private investment, contributing to an environment where companies create competitive advantages. Evident the need for efforts to ensure that municipalities think of public policies together with the governments of region; and, with State aid, can improve the indicators presented, creating development poles that resonates in improvements in quality of life for society